Bartonella Endocarditis-Associated Glomerulonephritis: A Mimicker of Autoimmunity and Vasculitis - Nicole K. Andeen; Vanderlene L. Kung; Jane K. Nguyen; Rupali S. Avasare; Georges N. Nakhoul; Nabin K. Shrestha; Jina T. Makadia; Tricia Jesperson; Cynthia C. Nast; Grace (Hae Yoon) Choung; Leal Herlitz (Kidney International Reports)
Introduction: Bartonella spp. are highly fastidious gram-negative facultative intracellular bacteria which can cause a culture-negative infective endocarditis (IE) with unique clinicopathologic features. Methods: In this study, we assembled 20 cases of glomerulonephritis (GN) due to Bartonella IE from 3 institutions and compared them with 49 cases of culture-positive IEGN and 30 cases of non-endocarditis infection-related GN (IRGN). Results: IEGN was seen in approximately 0.15% to 0.4% of native renal biopsies, with Bartonella causing 8% to 21% of IEGN. Patients with Bartonella IEGN had preexisting cardiac valve alterations (75%); antineutrophil cytoplasmic autoantibody (ANCA) positivity (67%); hypocomplementemia (75%); antinuclear antibody positivity (53%); cryoglobulinemia (45%); and hematologic manifestations, including B-symptoms (79%), splenomegaly (59%), thrombocytopenia (83%), and pancytopenia (44%). In 75% of the cases, Bartonella endocarditis was not diagnosed until after kidney biopsy. Pathologically, Bartonella IEGN presented as a focally crescentic GN, which was C3 codominant (80%) with strong IgM (65%) and/or C1q (55%), or pauci-immune (10%), with predominantly mesangial deposits and limited exudative features. At a median follow-up time of 15 months, progression to end-stage kidney disease (ESKD) for all-comers with IEGN was associated with higher creatinine levels at diagnosis, presence of nephrotic syndrome, female sex, and C1q staining intensity. Although delayed diagnosis of infection and immunosuppressive therapy for presumed autoimmune disease before kidney biopsy were more common in Bartonella IEGN than in culture-positive IEGN, neither were associated with ESKD. Conclusion: IEGNs share laboratory and biopsy features with autoimmunity, which may obfuscate identification of underlying bacterial infection.